IMPLEMENTATION OF AN ALGORITHM FOR SQUARE ROOT COMPUTATION IN AN FPGA ARRAY BY USING FIXED POINT REPRESENTATION (2018)
The implementation of the square root computation in an FPGA device is presented in this work. The calculation is not one of convergence type, so the accuracy is very high and there are no conditions or restrictions for the operation to be fulfilled. It also consumes much less hardware surface than other algorithms for calculating the square root of a number. The number entered is of fixed-point representation, it is parameterizable, that is, two constants N and M can define the size of the number, where N defines the number of bits in the integer part of the number and M defines the number of bits of the fractional part.